How Can Public Sector Organizations Enhance Employee Loyalty? The Impacts of Ethical Leadership, Employee Job Satisfaction, and Employee Motivation - Mohamed Abdi, Ahmed-Nor; Hashi, Mohamed Bile (2024)
Numerous scandals and failures within governmental entities have drawn significant attention to ethical leadership. This study examined how public sector ethical leadership influences worker loyalty in Somalia through the underlying mechanisms of worker motivation and worker job satisfaction. Using an online cross-sectional quantitative design, we collected data from 300 public sector employees across numerous federal ministries in Mogadishu, Somalia. We analyzed the data using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that public sector ethical leadership, employee motivation, and job satisfaction positively and significantly affect employee loyalty. Furthermore, public sector ethical leadership positively and significantly affects workers’ motivation and job satisfaction. Finally, the findings show that public sector worker motivation and worker job satisfaction partially mediate the relationship between public sector ethical leadership and worker loyalty. The current study offers novel perspectives on the mediating effect of worker job satisfaction and motivation on the association between public sector ethical leadership and worker loyalty. The current study empirically outlines the significance of public sector ethical leadership, worker motivation, and job satisfaction in fostering worker loyalty in the setting of Somali governmental entities. Thus, to satisfy employees and increase their loyalty, policymakers and administrators in the Somali public sector should support ethical leadership, implement inspiring programs, and foster a positive work environment.